Evolutionary and Developmental Modules - Lacquaniti, Francesco; Ivanenko, Yuri P.; D'avella, Andrea; Zelik, Karl; Zago, Myrka (Frontiers in Computational Neuroscience, 2013)
The identification of biological modules at the systems level often follows top‐down decomposition of a task goal, or bottom‐up decomposition of multidimensional data arrays into basic elements or patterns representing shared features. These approaches traditionally have been applied to mature, fully developed systems. Here we review some results from two other perspectives on modularity, namely the developmental and evolutionary perspective. There is growing evidence that modular units of development were highly preserved and recombined during evolution. We first consider a few examples of modules well identifiable from morphology. Next we consider the more difficult issue of identifying functional developmental modules. We dwell especially on modular control of locomotion to argue that the building blocks used to construct different locomotor behaviors are similar across several animal species, presumably related to ancestral neural networks of command. A recurrent theme from comparative studies is that the developmental addition of new premotor modules underlies the postnatal acquisition and refinement of several different motor behaviors in vertebrates.